2018
DOI: 10.1186/s41100-018-0173-8
|View full text |Cite
|
Sign up to set email alerts
|

Low serum albumin as a risk factor for infection-related in-hospital death among hemodialysis patients hospitalized on suspicion of infectious disease: a Japanese multicenter retrospective cohort study

Abstract: Background: Serum albumin is a marker of nourishment and inflammation. Although hypoalbuminemia in hemodialysis patients is reported as a risk factor for poor prognosis, few studies describe its effects on infectious diseases specifically. This study aimed to examine the relationship between the serum albumin level on admission and infection-related in-hospital death among hemodialysis patients. Methods: This was a multicenter retrospective observational study that was undertaken in Japan. We reviewed the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…However, exaggerated synthesis of interleukin 6 can lead to an acute, severe systemic inflammatory response syndrome (SIRS) known as ‘cytokine storm’ [ 192 ]. In addition to SIRS, hypoalbuminemia and lymphopenia were previously shown to be associated with increased odds of severe infection and infection-related death [ [193] , [194] , [195] ]. Complications were very common amongst patients with severe COVID-19 disease (over 50%) and non-survivors (more than two thirds).…”
Section: Discussionmentioning
confidence: 99%
“…However, exaggerated synthesis of interleukin 6 can lead to an acute, severe systemic inflammatory response syndrome (SIRS) known as ‘cytokine storm’ [ 192 ]. In addition to SIRS, hypoalbuminemia and lymphopenia were previously shown to be associated with increased odds of severe infection and infection-related death [ [193] , [194] , [195] ]. Complications were very common amongst patients with severe COVID-19 disease (over 50%) and non-survivors (more than two thirds).…”
Section: Discussionmentioning
confidence: 99%
“…Albumin (ALB) tends to decrease in levels during acute infections and is a strong indicator of outcome in infectious diseases. The relationship between low serum albumin level and high mortality has been reported in several studies [15,16].…”
Section: Introductionmentioning
confidence: 82%
“…It could be a risk factor by affecting the free fraction of the drug interacting with the drug receptor [29]. With that being said, Minatoguchi et al’s [30] findings showed that the serum albumin level was a significant risk factor for infection-related in-hospital death among hemodialysis patients.…”
Section: Discussion/conclusionmentioning
confidence: 99%